Faktor yang Mempengaruhi Manajemen Sumber Daya Manusia dalam Strategis Rekruitmen Tenaga Kerja - Manaf, Tegar Abdillah; Arnu, Anggi Pasca (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research explores the factors that influence human resource management in workforce recruitment strategies. Through in-depth analysis of related literature, this research identifies key variables such as technology, organizational policies, and labor market dynamics as determining factors in the success of recruitment strategies. The findings of this research provide insight into how organizations can optimize their human resource management, align recruiting practices with environmental changes, and maintain competitive advantage through timely and qualified workforce recruitment.